Prevalence of metabolic syndrome among middle aged women in Babol, Iran - Delavar, Mouloud Agajani; Lye, Munn Sann; Khor, Geok Lin; Hanachi, Parichehr; Syed Hassan, Syed Tajuddin (Seameo Regional Tropical Medicine & Public Health, 2009)
Metabolic syndrome is a cluster of interconnected cardiovascular risk factors. This research determined the prevalence of metabolic syndrome by body mass index, sociodemography, and lifestyle habits of women 30-50 years old in Babol Iran. A systematic random sampling was used to select 984 middle aged women from an urban area in Babol, Mazandaran, Iran. Screening was used to select eligible women who fulfilled selection criteria. The Adult Treatment Panel III (ATP III) criteria were used to classify participants as having metabolic syndrome. The overall prevalence of metabolic syndrome was 31.0%. Abdominal obesity was observed in about 76.6% (n = 273) of subjects. The prevalences of hypertension, high fasting blood glucose, high triglycerides and low HDL-cholesterol were 12.1, 12.1, 41.5 and 48.6%, respectively. Older age (OR=2.07; CI=1.56-2.75), higher waist circumference (OR=6.46; 95% CI=3.48-11.96), higher systolic (OR=3.84; 95% Cl=2.37-6.22) and diastolic blood pressure (OR=1.89; 95% CI=1.17-3.05), low education level (OR=2.780; CI=1.80-4.31), housekeeping (OR=3.92; CI=1.24-12.44) and farming occupation (OR=20.54; 95% CI=3.54-119.06) were associated with increased risk for metabolic syndrome. The odds ratio (OR) showed no significant associations between metabolic syndrome and smoking or exposure to smoking. This study showed high prevalence of metabolic syndrome in Iranian middle aged women. A larger area and population study is needed to enable broader recommendations for the prevention of metabolic syndrome.